If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 1) + 2(2x + -6) = 33 Reorder the terms: 3(1 + x) + 2(2x + -6) = 33 (1 * 3 + x * 3) + 2(2x + -6) = 33 (3 + 3x) + 2(2x + -6) = 33 Reorder the terms: 3 + 3x + 2(-6 + 2x) = 33 3 + 3x + (-6 * 2 + 2x * 2) = 33 3 + 3x + (-12 + 4x) = 33 Reorder the terms: 3 + -12 + 3x + 4x = 33 Combine like terms: 3 + -12 = -9 -9 + 3x + 4x = 33 Combine like terms: 3x + 4x = 7x -9 + 7x = 33 Solving -9 + 7x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 9 + 7x = 33 + 9 Combine like terms: -9 + 9 = 0 0 + 7x = 33 + 9 7x = 33 + 9 Combine like terms: 33 + 9 = 42 7x = 42 Divide each side by '7'. x = 6 Simplifying x = 6
| 3x^3+2x^2+-41x+-66=0 | | 8a-48=-6(-6-6a) | | 6(2-3x)=4(5x+7) | | 2(5*555*5)-56= | | 5y+60-9=12+8y-72 | | 200*50+20= | | 9m+5=9m+6 | | m=n-7 | | -34m=12 | | 2x-9y=-3 | | 0=12x+4.9x^2 | | 90-6x=100-8x | | 2(6x-6)+3=2(2x+3)+5 | | 8x-4=10x+19 | | 9xz^2-30xz-96x= | | -2x-7(c+3)=-93 | | 1(a-4)=2(2a+4) | | 8x-4=10+19 | | 4-3yi=4x+16i | | -329=-7(7+5p) | | x=0.5+y | | 3(4x-7)=6-(2-5x) | | 8(-8k-1)=5k-8 | | -11=9-2b | | 31=25-x-x | | 4(2x-7)+4=8 | | 3x+4y-z=4 | | 4x+9=10x+3 | | -59=-4n-3 | | 8-3x+2x=3(x+4) | | 25-7v=10(v-6) | | F(x)=105x |